Investigation On Seismic Response Of 3D Symmetric Single Story of RC Frame With RC Infill Wall - Mochamad Firmansyah Sofianto; Huei Tser Chen (Department of Civil Engineering, Faculty of Engineering, University of Brawijaya, 2013)
Infill wall is commonly used on construction to enclosure the building and to divide the large area, however they are treated as non-structural on the structural design. In this study, the effect of variation width of infill wall on 3D symmetric single-story frame and the material using assumed as RC material was conducted to understand the contribution for reducing the internal force and for increasing the natural frequencies. From the investigation, the natural frequency and internal force of 3D symmetric model with variation width of RC infill wall increase and decrease respectively if compared with 3D pure frame model. From this investigation, it is better to have the walls on both sides of the column to have better reduction in the internal force, and the effect of floor diaphragm assumption explain that its effect only increase a little frequency and internal force, but the impact of model design is affected the rigid stiffness of beam-slab model. Thus, consideration of RC infill wall or the wall element on the structure model on the seismic response is recommended to become study investigation.